Protracted maternal malnutrition induces aberrant changes in maternal uterine artery hemodynamics and the metabolic profiles of the dam and neonate - Thorson, Jennifer F.; Prezotto, Ligia D. (Frontiers in Physiology, 2024)
Malnutritional stress during gestation is a well-established driver of metabolic disfunction in offspring. Extended exposure to malnutrition requires metabolic plasticity as the animal shifts toward a catabolic state. In this paper we demonstrate the influence of malnutrition throughout gestation on uterine artery hemodynamics and the metabolism of the dam and neonate. We hypothesized that gestational malnutrition reduces blood flow of the maternal uterine artery and regulates the metabolic profile of the dam and offspring. Further, the combination of these factors consequently influences the concentration of metabolites in the cerebrospinal fluid of the neonate at birth. To test our hypotheses, pregnant cows caring a single female fetus were assigned to treatments by age and body condition score to one of three individually-fed dietary treatments: Underfed, Control, or Overfed throughout gestation. Uterine blood flow was measured via transrectal Doppler ultrasonography in late gestation. Blood samples were collected from dams throughout gestation, and blood and cerebrospinal fluid were collected from neonates at birth to analyze concentration of metabolites. In the current report, we reveal that maternal malnutrition regulates uterine artery hemodynamics and the maternal metabolic profile throughout gestation. This is the first report to demonstrate that maternal undernutrition leads to an increase in the concentration of urea nitrogen in neonates. Finally, a concentration gradient of metabolites from the dam to neonatal cerebrospinal fluid was observed, which may have potential implications for central nervous system development. These findings not only illustrate the complexity of the maternal-to-fetal interaction required to support the growth of the fetus and homeostasis of the dam but also reveals a novel avenue for investigating the influence of protracted maternal malnutrition on metabolic pathway preferences in offspring. Moreover, these findings are of paramount importance in the development of intervention strategies for morbid neonates.